The effects of nest cover types on incubation period and hatching rate of Olive Ridley turtle Lepidochelys olivacea in the Turtle Conservation Unit, Pariaman - Dwi Pitriani; M. Fauzi; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The incubation period and hatching rate of turtle eggs are influenced by temperature and humidity of the nest, thus the type of materials used for covering the nest may affects the incubation period and hatching rate of the eggs. To understand the suitable nest cover for Lepidochelys olivacea eggs, a study has been conducted in March - May 2017. The types of cover used were plastic tarp, tin , and Terminalia catappa leaves. Results shown that the types of cover affects the incubation period and hatching rate of the turtle eggs, there were 60% and 60 days incubation (no cover), 77.7 % and 59.33 days incubation (plastic tarp), 68.8 % and 59.33 days (tin) and 84.4% with incubation period 59.33 days (T. catappa leaves).Key words : Hatcing rate,Olive Ridley Turtle, Nest cover, Turtle Conservation Unit, Pariaman